Bašeskijine folklorističke zabilješke / Bašeskija's Folkloristic Notes: "Predskazanja i snovi" / 'Predications and Dreams' - Šemsović, Sead (Pregled: časopis za društvena pitanja / Periodical for social issues, 2017)
Predictions of future events and dreams, where we distinguish general dreams, dreams as a result of Istikhaarah prayer done by the chronicler either for himself or for someone else, and those related to Istikhaarah prayers performed on behalf of Bašeskija occupy a special place in Bašeskija's field of interests. These notes reflect the specificities of Muslim beliefs in Sarajevo in the second half of the 18th century.